SISTEM INFORMASI PEMESANAN TIKET BUS PADA PT. BINTANG TANI JAYA(BTN) BERBASIS WEBSITE - Br. Hombing, Betseba; Siringoringo, Rimbun; Simamora, Roni J. (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2023)
The Web-Based Bus Ticket Reservation Information System at PT. Bintang Tani Jaya (BTN) is an application aimed at facilitating the process of online bus ticket reservation for customers of PT. Bintang Tani Jaya. This application is designed using web-based technology, enabling customers to easily book bus tickets through internet-connected devices. The system integrates crucial features such as checking bus schedule availability, selecting travel routes, choosing seats, and making secure online payments. Using keywords such as bus ticket reservation, PT. Bintang Tani Jaya, web-based, and online application, this system is expected to enhance the efficiency of bus ticket reservation services, providing convenience and ease for customers.